Geographical Debate on COVID-19’s Impact on Healthcare Access and Utilization in Vulnerable Malaysian Communities - Lay Im Lim; Mohammad Javad Maghsoodi Tilaki; Sharifah R. S. Dawood; Su Jinxia (Societies)
The COVID-19 pandemic has amplified concerns about healthcare access, particularly among vulnerable populations. This study extends Andersen’s behavioral model to investigate how fear of high-risk locations, alongside predisposing, enabling, and need factors, shapes healthcare-seeking behavior in Penang, Malaysia. A survey of 211 individuals (58% response rate) was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results reveal that need factors—specifically self-rated health and chronic illness—strongly predict healthcare utilization. However, this relationship is moderated by fear of infection, leading some high-risk individuals to forgo care despite medical necessity. Enabling factors, including financial resources and access to public healthcare, showed limited influence, likely due to Malaysia’s universal healthcare system and growing use of telemedicine. Older adults maintained healthcare utilization among predisposing variables, while higher-educated individuals were more cautious, possibly due to heightened health literacy and trust in digital alternatives. Although fear influenced care-seeking behavior for minor ailments, it did not significantly deter individuals from accessing services for severe conditions. These findings underscore the nuanced interaction between psychosocial factors and institutional context in shaping healthcare decisions during health crises.